Comparative analysis of genomic characteristics, fitness and virulence of MRSA ST398 and ST9 isolated from China and Germany - Xing Ji; Henrike Krüger; Jin Tao; Yaxin Wang; Andrea T. Feßler; Rina Bai; Shaolin Wang; Yanjun Dong; Jianzhong Shen; Yang Wang; Stefan Schwarz; Congming Wu (Emerging Microbes and Infections)
Methicillin-resistant Staphylococcus aureus (MRSA) of sequence types ST398 and ST9 are dominant lineages among livestock in Europe and Asia, respectively. Although both STs were commonly found as colonizers of the skin and the mucosal membranes, MRSA ST398, rather than MRSA ST9, has been reported to cause infections in humans and animals. Herein, we comparatively analyzed the genomic characteristics, fitness and virulence of MRSA ST398 and ST9 isolated from pigs in both China (CHN) and Germany (GER) to explore the factors that lead to differences in their epidemics and pathogenicity. We observed that the CHN-MRSA ST9 and the GER-MRSA ST9 have evolved independently, whereas the CHN-MRSA ST398 and GER-MRSA ST398 had close evolutionary relationships. Resistance to antimicrobial agents commonly used in livestock, the enhanced ability of biofilm formation, and the resistance to desiccation contribute to the success of the dominant clones of CHN-MRSA ST9 and GER-MRSA ST398, and the vwbνSaα gene on the genomic island might in part contribute to their colonization fitness in pigs. All MRSA ST398 strains revealed more diverse genome structures, higher tolerance to acids and high osmotic pressure, and greater competitive fitness in co-culture experiments. Notably, we identified and characterized a novel hysAνSaβ gene, which was located on the genomic island νSaβ of MRSA ST398 but was absent in MRSA ST9. The enhanced pathogenicity of the MRSA ST398 strains due to hysAνSaβ might in part explain why MRSA ST398 strains are more likely to cause infections.